Power Output and Efficiency During Supine, Recumbent, and Upright Cycle Ergometry - Wehrle, Anja; Waibel, Sarah; Gollhofer, Albert; Roecker, Kai (Frontiers in Sports and Active Living, 2021)
Recumbent and supine cycling are common exercise modes in rehabilitation and clinical settings but the influence of postures on work efficiency is unclear. Therefore, the aim of this study was to compare metabolic and ventilatory efficiency during upright, recumbent, and supine postures. Potential differences should be assessed for suitable diagnostics and for prescriptions of training that probably is performed in alternative postures. Eighteen healthy subjects (age: 47.2 ± 18.4 years; 10 female, 8 male) participated in the study and each completed three incremental cycle ergometer tests until exhaustion in upright, recumbent (40°), and supine positions. Gas exchange, heart rate (HR), and lactate concentrations were analyzed and efficiency was calculated subsequently. Testing sessions were performed in random order within a 2-week period. Upright cycling resulted in significantly higher peak values [power output, oxygen uptake (Vo2), HR] as well as performance at lactate and ventilatory thresholds in comparison to recumbent or supine positions. Vco2/Vo2 slope and ventilatory efficiency (VE/Vco2 slope) were not affected by posture. Aerobic work efficiency (Vo2/P slope) and gross efficiency (GE) differed significantly between postures. Hereby, GE was lowest in supine cycling, particularly obvious in a mainly aerobic condition at 70 Watt [Median 11.6 (IQR 10.9–13.3) vs. recumbent: 15.9 (IQR 15.6–18.3) and upright: 17.4 (IQR 15.1–18.3)]. Peak power as well as GE and work efficiency values are influenced by cycling position, reinforcing the importance of adjusting test results for training prescriptions. Surprisingly, ventilatory efficiency was not affected in this study and therefore does not seem to falsify test results for pulmonary diagnostics.